Mesej Dakwah Para Rasul (A.S.) Kepada Golongan Pembesar Negara - Zawawi, Yusoff (2014)
Da`wah or preaching is the main task of the Prophets (a.s). Their most difficult and challenging target group are the aristocrats of the state leaders. This article discusses the Prophet‟s (a.s) messages through their da`wah activities to the aristocrats. Comprehensive study about these messages are done through content analysis of the related Quranic verses and Hadith as well as from history books to identify the type of messages that are suitable for this group of people. The research finding shows that these da`wah messages of the Prophets (a.s) are based on the approach of accommodating the message with the target group. It is also found that the process of accommodating the message with the target group can be done by understanding the situation and the background of the target group especially through the aspect of sociology and psychology. The finding gives the implication that preachers‟s understanding of the sociology and psychology of the aristocrats is important to identify the suaitable message to them.